Topical Application of Linezolid–Loaded Chitosan Nanoparticles for the Treatment of Eye Infections - Musaed Alkholief; Mohd Abul Kalam; Abdullah K. Alshememry; Raisuddin Ali; Sulaiman S. Alhudaithi; Nasser B. Alsaleh; Mohammad Raish; Aws Alshamsan (Nanomaterials, 2023)
Linezolid (LZ) loaded chitosan–nanoparticles (CSNPs) was developed by the ionic–gelation method using Tripolyphosphate–sodium as a crosslinker for topical application for the treatment of bacterial eye infections. Particles were characterized by Zeta–Sizer (Malvern Nano–series). TEM was used for structural morphology. Encapsulation and drug loading were estimated by measuring the unencapsulated drug. In-vitro drug release in STF (pH 7) was performed through a dialysis membrane. Storage stability of LZ–CSNPs was checked at 25 °C and 40 °C for six months. The antimicrobial potency of NPs was evaluated on different Gram–positive strains. Ocular irritation and pharmacokinetic studies were completed in rabbits. Ex-vivo transcorneal permeation of the drug was determined through the rabbit cornea. Ionic interaction among the oppositely charged functional groups of CS and TPP generated the CSNPs. The weight ratio at 3:1, wt/wt (CS/TPP) with 21.7 mg of LZ produced optimal NPs (213.7 nm with 0.387 of PDI and +23.1 mV of ZP) with 71% and 11.2% encapsulation and drug loading, respectively. Around 76.7% of LZ was released from LZ–AqS within 1 h, while 79.8% of LZ was released from CSNPs at 12 h and 90% at 24 h. The sustained drug release property of CSNPS was evaluated by applying kinetic models. The linearity in the release profile suggested that the release of LZ from CSNPs followed the Higuchi–Matrix model. LZ–CSNPs have shown 1.4 to 1.6-times improved antibacterial activity against the used bacterial strains. The LZ–CSNPs were “minimally–irritating” to rabbit eyes and exhibited 4.4-times increased transcorneal permeation of LZ than from LZ–AqS. Around 3-, 1.2- and 3.1-times improved Tmax, Cmax, and AUC0–24 h, respectively were found for LZ–CSNPs during the ocular pharmacokinetic study. AqS has shown 3.1-times faster clearance of LZ. Conclusively, LZ–CSNPs could offer a better alternative for the prolonged delivery of LZ for the treatment of bacterial infections in the eyes.